Chemoenzymatic Cascades for the Enantioselective Synthesis of β‐Hydroxysulfides Bearing a Stereocentre at the C−O or C−S Bond by Ketoreductases. Issue 31 (10th June 2022) - Zhao, Fei; Lauder, Kate; Liu, Siyu; Finnigan, James D.; Charnock, Simon B. R.; Charnock, Simon J.; Castagnolo, Daniele
Abstract: Chiral β‐hydroxysulfides are an important class of organic compounds which find broad application in organic and pharmaceutical chemistry. Herein we describe the development of novel biocatalytic and chemoenzymatic methods for the enantioselective synthesis of β‐hydroxysulfides by exploiting ketoreductase (KRED) enzymes. Four KREDs were discovered from a pool of 384 enzymes identified and isolated through a metagenomic approach. KRED311 and KRED349 catalysed the synthesis of β‐hydroxysulfides bearing a stereocentre at the C−O bond with opposite absolute configurations and excellent ee values by novel chemoenzymatic and biocatalytic‐chemical‐biocatalytic (bio‐chem‐bio) cascades starting from commercially available thiophenols/thiols and α‐haloketones/alcohols. KRED253 and KRED384 catalysed the enantioselective synthesis of β‐hydroxysulfides bearing a stereocentre at the C−S bond with opposite enantioselectivities by dynamic kinetic resolution (DKR) of racemic α‐thioaldehydes. Abstract : Four ketoreductases (KREDs) were identified for the enantioselective synthesis of β‐hydroxysulfides. KRED311 and KRED349 catalyse the synthesis of β‐hydroxysulfides bearing a stereocentre at the C−O bond with opposite absolute configurations via chemoenzymatic cascades from thiophenols/thiols and α‐haloketones/alcohols. KRED253 and KRED384 catalyse the synthesis of β‐hydroxysulfides bearing a stereocentre at the C−S bond with opposite enantioselectivities by dynamic kinetic resolution (DKR) of racemic α‐thioaldehydes.